Implementasi Program SAKTI Dalam Pembelajaran Bahasa Arab Di SMP Queen Ibnu Sina Genteng Banyuwangi - Zahro, Mualifatuz; Kholiq, Ilham Nur (Universitas KH. Mukhtar Syafaat, 2025)
The purpose of the study was to determine the implementation of the SAKTI takhasus program in Arabic language learning at SMP Queen Genteng. and qualitative methods were used as research methods with research instruments in the form of observation, interviews and documentation. The results of the study indicate that the SAKTI takhasus program at SMP Queen Ibnu Sina is a program that is implemented sustainably, with the AIR (auditory intellectually repetition) method and the teaching materials used are three books or books, such as the Mufrad?t amtsilati Book, LKS, and the Durusulllughoh Al-Arabiyyah Book. while supporting factors in the implementation of the program such as learning motivation, sufficient teaching staff, and students' readiness to learn in the field of Arabic. and inhibiting factors in the implementation of the program such as inadequate facilities and infrastructure, students who are often late, students who often sleep in class, students' backgrounds are elementary school graduates (not MI) and are less accustomed to mufr?dat.